Impact of Home Fitness Program on Anthropological Characteristics of Physically Active and Physically Inactive People - Gordana Furjan-Mandic; Biljana Bilbija; Josipa Radas; Gordana Ivkovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Main purpose of this work is presentation of a complex program that consists of simple program content focusing towards targeted change of important anthropological characteristics. To achieve the objective, authors created "stay at home" fi tness program with simple exercise content which is adjusted for both trainees based on their fi tness level. The sample is defi ned as a pattern of two trainees. One exerciser is male and physically inactive and the other is female and physically active. The initial and fi nal state of the subjects is determined with 4 tests for assessment of morphological characteristics and 6 tests for assessment of moto abilities. For comparison of the measured results of the initial and fi nal state of the respondents we used the method of calculating the diff erence expressed as a percentage, using the "Microsoft Excel". After completing treatment, we've observed positive changes in all measures for the assessment of anthropological status, for trained and untrained persons.